Survey of Elementary School Teacher Needs on Video Learning Mathematics Based on Contentextual Teaching and Learning in Pelembang City - Astika, Ruri Tria; Astra, I Made; Makmuri, Makmuri; Sumarni, Sri; Andika, Windi Dwi; Palupi, Endah Kinarya (Al-Jabar: Jurnal Pendidikan Matematika, 2019)
This study aims to gather information about the needs of elementary school teachers in the application of effective mathematics learning. This research is part of a research entitled Development of Learning Videos Based on Contextual Teaching and Learning Approaches to Improve Student Learning Outcomes of Primary Schools in Palembang City. The method used is research and development in the form of survey data. The survey method was carried out using a questionnaire in the Google form on 39 teachers in Palembang. The results of the distribution of the questionnaire interpreted that elementary school teachers were in dire need of media, especially in the form of contextual based mathematics learning videos. The conclusion of this research is the need for the development of learning videos to facilitate teachers in teaching contextual mathematics so that it will have a good impact on learning outcomes of elementary school students.